VECTOR ERROR CORRECTION MODEL (VECM) APPROACH IN ANALYZING THE DYNAMIC RELATIONSHIP BETWEEN GROSS DOMESTIC PRODUCT (GDP) AND ISLAMIC BANK FINANCING IN INDONESIA - Zulkarnain, Riyan; Nasrulloh, Nasrulloh; Izzati Septiana, Nurul (Ekonomi Islam, 2025)
Research aims: This study investigates the connection between Islamic bank financing and the Gross Domestic Product (GDP) of Indonesia. Design/Methodology/Approach: Using secondary time-series data (2015 – 2023), this study employs the Vector Error Correction Model (VECM) within a quantitative framework to investigate short-run and long-run dynamics between the two variables. Research findings: This study reveals that Islamic financing is a key factor in fostering long-term economic growth, although its influence in the short term shows a fluctuating pattern. The Granger test indicates bidirectional causality, while the IRF and VD analyses show an initial positive impact of Islamic financing on GDP that diminishes over time. Theoretical Contribution/Originality: This study develops the theoretical framework of Islamic banking by demonstrating that financing is directed toward the real sector based on principles of justice (free of interest and speculation) and isolated from non-bank variables, such that funding can foster pure economic growth. Practitioners/Policy Implications: To achieve the real-world impact of Islamic financing on the national economy, close collaboration between financial regulators, academics, industry stakeholders, and Islamic social organizations is essential. Research Limitations/Implications: The overall scope of the data used remains limited, particularly regarding the exclusion of external variables such as global economic dynamics, the level of financial inclusion, and fiscal policies, which may implicitly influence the research outcomes.